A 21650 full-tab cylindrical lithium ion battery

CN123018162APending Publication Date: 2026-10-30JIANGSU RELIANCE ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611000947.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-07
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提供一种21650全极耳圆柱锂离子电池,旨在解决现有21650圆柱锂离子电池存在的以上问题

Benefits of technology

本发明通过对21650圆柱电池进行精准的结构参数与性能参数匹配设计,提升了电池整体的能量密度,本发明摒弃了片面追求极片压实或提高卷芯能量密度来提升电池整体能量密度上限的方案,转而将电池壳体的空间尺寸与电池卷芯能量密度的比例要素纳入到电池性能设计优化的范围,提供了一种新的电池性能优化设计方向,利于电池性能的进一步提升。本发明优化设计的电池壳体与电池卷芯的能量密度参数比,实现材料比能与封装空间利用率的双向最优平衡,避免卷芯能量密度虚高而实际电池能量提升有限的弊端。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018162A_ABST
    Figure CN123018162A_ABST
Patent Text Reader

Abstract

The application relates to the field of lithium ion batteries, and particularly discloses a 21650 full-tab cylindrical lithium ion battery, which comprises a battery shell, a battery roll core and electrolyte packaged in the shell; the shell has an outer diameter of 20.8-21.2 mm and a height of 64.8-65.2 mm, the roll core has an energy density of 270-330 Wh / kg, and the energy density to shell volume ratio is 11.9-14.8 Wh / (kg*cm3); the battery roll core comprises a positive electrode sheet, a negative electrode sheet and a separator, the positive electrode sheet comprises positive electrode active material, the positive electrode active material is formed by mixing polycrystal particles and single crystal particles, the polycrystal particles have a chemical general formula of Li a Ni b Co c Mn d Al e O2, and the single crystal particles have a chemical general formula of Li x Ni y Co z Mn m Al n O2; the negative electrode sheet comprises a negative electrode material, the negative electrode material comprises graphite, silicon carbon and porous carbon, the porous carbon has a pore diameter of 2-50 nm, and the content of the porous carbon material is 0.5-5 wt%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery technology, specifically to a 21650 all-tab cylindrical lithium-ion battery. Background Technology

[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles and energy storage systems due to their high energy density and long cycle life. Among them, 21650 lithium-ion batteries, as large-size cylindrical batteries, have a wide range of market applications due to their wide adaptability and high structural strength.

[0003] However, existing 21650 cylindrical batteries still have many shortcomings that restrict their large-scale application. For example: ① Regarding cathode materials: Existing high-nickel ternary cathode materials mostly use single-crystal or polycrystalline particles. Single-crystal particles have problems such as many grain boundaries, easy structural collapse during cycling, and accelerated electrolyte erosion, resulting in rapid capacity decay and short cycle life. While single-crystal particles have better structural stability, they have defects such as low compaction density and slow ion conduction rate, making it difficult to achieve both high energy density and high cycle stability, and thus unable to meet the needs of high-energy-density batteries. ② Regarding anode materials: Anode materials are one of the key factors determining the performance of lithium-ion batteries. Graphite has become the most commonly used anode material in traditional lithium-ion batteries due to its stable structure, good conductivity, and low cost. However, the theoretical specific capacity of graphite materials is relatively low (approximately 372 mAh / g), making it difficult to achieve high specific capacity. To meet the demand for high energy density, the industry has gradually introduced silicon-carbon composite materials to replace some graphite materials to overcome the energy density bottleneck. This leverages the high specific capacity of silicon-based materials to improve the overall energy density of the battery. However, silicon-carbon materials exhibit a significant volume expansion effect during charging and discharging, which can easily lead to cracking of the negative electrode and shedding of active materials, resulting in a significant increase in battery internal resistance and a marked decrease in cycle performance. Furthermore, the combination of silicon-carbon composite materials and graphite materials creates disordered pore structures and uneven ion transport channels within the electrodes, exacerbating battery polarization and significantly reducing rate performance and cycle stability. Additionally, parameter design mismatch exists: existing 21650 cylindrical batteries lack precise structural and performance parameter matching designs, leading to low battery casing space utilization and insufficient release of battery core performance, resulting in a lower overall energy density limit and difficulty in achieving high specific energy indicators.

[0004] In summary, existing 21650 cylindrical lithium-ion batteries generally suffer from low energy density, poor compatibility of positive and negative electrode materials, insufficient cycle stability, and a relatively low upper limit of energy density. Therefore, there is an urgent need to design a high-performance 21650 all-tab cylindrical lithium-ion battery to address the numerous shortcomings of existing technologies. Summary of the Invention

[0005] The purpose of this invention is to provide a 21650 all-tab cylindrical lithium-ion battery, which aims to solve the above-mentioned problems existing in the current 21650 cylindrical lithium-ion battery.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solution: This invention provides a 21650 all-tab cylindrical lithium-ion battery, which includes a battery casing and a battery core and electrolyte encapsulated in the battery casing; The outer diameter of the battery casing is 20.8–21.2 mm and the height is 64.8–65.2 mm. The energy density of the battery core is 270–330 Wh / kg. The energy density of the battery core to the volume ratio of the battery casing is 11.9–14.8 Wh / (kg·cm³). The battery core includes a positive electrode sheet, a negative electrode sheet, and a separator. The positive electrode sheet includes a positive electrode active material. Based on 100g by weight, the positive electrode active material is composed of polycrystalline particles and monocrystalline particles mixed in a weight ratio of (60-85):(15-40). The general chemical formula of the polycrystalline particles is Li a Ni b Co c Mn d Al e O2, where 0.95≤a≤1.05, 0.85≤b≤0.92, 0.03≤c≤0.10, 0.01≤d≤0.10, 0.01≤e≤0.05, b+c+d+e=1; The chemical formula of the single crystal particles is Li x Ni y Co z Mn m Al n O2, in the formula, 0.95≤x≤1.05, 0.85≤y≤0.95, 0.02≤z≤0.08, 0.01≤m≤0.06, 0.01≤n≤0.04, y+z+m+n=1; The negative electrode sheet includes a negative electrode material, which includes at least graphite-based materials, silicon-carbon composite materials, and porous carbon materials. The pore size of the porous carbon material is 2-50 nm, and the content of the porous carbon material in the negative electrode material is 0.5-5.0 wt%.

[0007] Specifically, the 21650 all-tab cylindrical lithium-ion battery designed in this invention, by precisely setting the ratio of the battery core's energy density to the battery casing volume, avoids both the problem of low battery casing space utilization (large casing, small core) caused by excessively low energy density, and the problem of excessively high energy density leading to excessive core compaction, difficulty in electrolyte wetting, and insufficient core performance release, thus resulting in a low upper limit of the overall battery energy density. This invention overcomes the problem of existing 21650 cylindrical batteries having a low upper limit of overall battery energy density and failing to meet high specific energy requirements due to unreasonable parameter matching between casing size and core energy density.

[0008] Furthermore, a 21650 all-tab cylindrical lithium-ion battery: the BET specific surface area of ​​the porous carbon material is ≤1000m² / g.

[0009] Furthermore, a 21650 all-tab cylindrical lithium-ion battery: the BET specific surface area of ​​the porous carbon material is 300-500 m² / g.

[0010] Furthermore, a 21650 all-tab cylindrical lithium-ion battery: the porous carbon material has a pore volume ≥ 0.1 cm³ / g.

[0011] Furthermore, in a 21650 all-tab cylindrical lithium-ion battery, the content of the silicon-carbon composite material in the negative electrode material is 5.0 to 20.0 wt%.

[0012] Furthermore, a 21650 all-tab cylindrical lithium-ion battery: the porous carbon material has a pore size of 2-10 nm.

[0013] Furthermore, a 21650 full-tab cylindrical lithium-ion battery: the half-width at half maximum (WHM) of the pore size distribution of the porous carbon material is ≤5.0 nm.

[0014] Furthermore, a 21650 all-tab cylindrical lithium-ion battery: the graphite material is at least one of artificial graphite or natural graphite.

[0015] Furthermore, a 21650 all-tab cylindrical lithium-ion battery: the method for preparing the negative electrode sheet includes: mixing graphite-based materials, silicon-carbon composite materials, and porous carbon materials in a solvent to form a negative electrode slurry; coating the negative electrode slurry onto the surface of a negative electrode current collector; and drying to obtain the negative electrode sheet of the lithium-ion battery. Specifically, deionized water is used as the solvent.

[0016] Furthermore, a 21650 all-tab cylindrical lithium-ion battery: the battery also meets at least one of the following conditions: (1) the negative electrode slurry further includes a binder selected from sodium carboxymethyl cellulose and / or styrene-butadiene rubber; (2) the electrolyte contains lithium hexafluorophosphate and at least one organic solvent selected from ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate; (3) the separator is a polyolefin microporous membrane or a ceramic-coated separator.

[0017] The beneficial effects of this invention are: This invention improves the overall energy density of 21650 cylindrical batteries by precisely matching their structural and performance parameters. It abandons the approach of solely pursuing electrode compaction or increasing core energy density to raise the upper limit of overall battery energy density. Instead, it incorporates the ratio of battery casing dimensions to core energy density into the battery performance design optimization, providing a new direction for battery performance optimization and facilitating further performance improvements. The optimized energy density ratio of the battery casing to the core achieves an optimal balance between material specific energy and packaging space utilization, avoiding the drawback of artificially high core energy density resulting in limited actual battery energy improvement.

[0018] This invention achieves the following excellent effects by employing a positive electrode active material system composed of single-crystal particles and polycrystalline particles: ① It balances high energy density and cycle stability: polycrystalline particles provide high specific capacity and good kinetics, while single-crystal particles are responsible for suppressing particle breakage, reducing interfacial side reactions, and improving high-temperature / long-term cycle life, thereby solving the problem that single polycrystalline or single-crystal particle materials cannot simultaneously meet the requirements of high specific energy and long cycle life; ② The combination of the two can regulate the uniformity of the internal pore structure of the positive electrode sheet, alleviate the stress concentration of the charge and discharge lattice, reduce the probability of microcracks in the electrode sheet, and significantly improve the cycle life of the core; ③ The preferred two particle materials have a high degree of matching in expansion and contraction rates, resulting in small overall deformation of the electrode sheet during cycling and good electrode sheet integrity. This can suppress the increase in the internal resistance of the core and avoid performance degradation. At the same time, the preferred combined positive electrode active material can also alleviate the gas generation problem commonly found in traditional positive electrode active materials, prevent battery core bulging, and significantly improve battery safety.

[0019] This invention employs a ternary composite anode material composed of graphite-based materials, silicon-carbon composite materials, and porous carbon materials. This material can improve the reversible specific capacity of the anode, effectively buffer the volume expansion of silicon-carbon, construct a fast ion-conducting network, and reduce electrode polarization, thereby enhancing the rate performance and cycle stability of the battery. In summary, this high-performance 21650 all-tab cylindrical lithium-ion battery overcomes many shortcomings of existing 21650 cylindrical batteries by optimizing battery casing size parameters, optimizing the configuration of positive and negative electrode materials, and precisely controlling the core performance parameters. Attached Figure Description

[0020] Figure 1 A schematic diagram of the external structure of the 21650 all-tab cylindrical lithium-ion battery provided by the present invention; Figure 2 A cross-sectional view of the 21650 all-tab cylindrical lithium-ion battery provided by the present invention; Figure 3 A schematic diagram of the internal structure of the 21650 all-tab cylindrical lithium-ion battery provided by the present invention. Figure 4 A schematic diagram of the positive electrode sheet in the battery core of the 21650 all-tab cylindrical lithium-ion battery provided by the present invention; Figure 5 This is a schematic diagram of the negative electrode sheet in the battery core of the 21650 all-tab cylindrical lithium-ion battery provided by the present invention.

[0021] The markings in the image are as follows: 1-Battery casing, 2-Battery core, 11-Positive electrode, 12-Negative electrode, 21-Positive electrode sheet, 22-Negative electrode sheet, 23-Center hole, 24-Negative electrode current collector, 211-Positive electrode active material layer area, 212-Positive electrode uncoated area, 213-Positive electrode sheet insulating coating area, 221-Negative electrode active material layer area, 222-Negative electrode uncoated area. Detailed Implementation

[0022] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the present invention or its application or use. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0023] Example 1

[0024] A 21650 all-tab cylindrical lithium-ion battery is provided, the battery comprising a battery casing and a battery core and electrolyte encapsulated in the battery casing; The battery casing has an outer diameter of 21.0 mm and a height of 65.0 mm. The battery core has an energy density of 300 Wh / kg. The ratio of the energy density of the battery core to the volume of the battery casing is approximately 13.33 Wh / (kg·cm³). The battery core includes a positive electrode sheet, a negative electrode sheet, and a separator. The positive electrode sheet includes a positive electrode active material, which, by weight 100, is composed of a mixture of polycrystalline particles and monocrystalline particles in a weight ratio of 75:25. The general chemical formula of the polycrystalline particles is LiNi. 0.88 Co 0.05 Mn 0.02 Al 0.05 O2; The chemical formula of the single crystal particles is LiNi. 0.92 Co 0.05 Mn 0.01 Al 0.02 O2; The electrolyte is 1 mol / L LiPF6, the solvent is EC / DMC / EMC (volume ratio 1:1:1), and 2.0% VC and 5.0% FEC are added; the separator is a polyolefin microporous membrane. The negative electrode sheet includes a negative electrode material, which comprises graphite-based materials, silicon-carbon composite materials, porous carbon materials, and a binder. The graphite-based materials are selected from artificial graphite (median particle size Dv50 of 10-20 μm). The silicon-carbon composite materials are commercially available deposited silicon-carbon materials with a silicon content of approximately 40-60%. The porous carbon materials have a pore size of 10.0 nm, a pore volume of 0.8 cm³ / g, and a BET specific surface area of ​​300 m² / g. The binder is sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR). The negative electrode material contains 84.5 wt% graphite-based materials, 12.0 wt% silicon-carbon composite materials, 2.5 wt% porous carbon materials, and the remainder is binder.

[0025] In Example 1, the wall thickness of the battery casing is 0.2 mm. The preparation process of the negative electrode is as follows: graphite materials, silicon-carbon composite materials and porous carbon materials are added to deionized water in proportion, CMC and SBR binders are added, and the mixture is stirred in a vacuum mixer to form a uniform slurry. The slurry is coated on the surface of the copper foil current collector, dried at 80°C, and then rolled to obtain the negative electrode sheet.

[0026] Example 2

[0027] The difference between Example 2 and Example 1 is that the content of porous carbon material in Example 2 is 0.5 wt%, the content of graphite material is 86.5 wt%, and the rest is the same as in Example 1.

[0028] Example 3

[0029] The difference between Example 3 and Example 1 is that the content of porous carbon material in Example 3 is 5.0 wt%, the content of graphite material is 82.0 wt%, and the rest is the same as in Example 1.

[0030] Example 4

[0031] The difference between Example 4 and Example 1 is that the content of silicon-carbon composite material in Example 4 is 5.0 wt%, the content of graphite material is 91.5 wt%, and the rest is the same as in Example 1.

[0032] Example 5

[0033] The difference between Example 5 and Example 1 is that the content of silicon-carbon composite material in Example 5 is 20.0 wt% and the content of graphite material is 76.5 wt%, while the rest is the same as in Example 1.

[0034] Example 6

[0035] The difference between Example 6 and Example 1 is that the pore size of the porous carbon material in Example 6 is 3.0 nm, while the rest is the same as in Example 1.

[0036] Example 7

[0037] The difference between Example 7 and Example 1 is that the pore size of the porous carbon material in Example 7 is 50.0 nm, while the rest is the same as in Example 1.

[0038] Example 8

[0039] The difference between Example 8 and Example 1 is that the pore size of the porous carbon material in Example 8 is 2.0 nm, while the rest is the same as in Example 1.

[0040] Example 9

[0041] The difference between Example 9 and Example 1 is that the BET specific surface area of ​​the porous carbon material in Example 9 is 100 m² / g, while the rest is the same as in Example 1.

[0042] Example 10

[0043] The difference between Example 10 and Example 1 is that the BET specific surface area of ​​the porous carbon material in Example 10 is 1000 m² / g, while the rest is the same as in Example 1.

[0044] Example 11

[0045] A 21650 all-tab cylindrical lithium-ion battery is provided, the battery comprising a battery casing and a battery core and electrolyte encapsulated in the battery casing; The battery casing has an outer diameter of 20.8 mm and a height of 64.8 mm. The battery core has an energy density of 270 Wh / kg. The ratio of the energy density of the battery core to the volume of the battery casing is approximately 12.27 Wh / (kg·cm³). The battery core includes a positive electrode sheet, a negative electrode sheet, and a separator. The positive electrode sheet includes a positive electrode active material, which, by weight 100, is composed of a mixture of polycrystalline particles and monocrystalline particles in a weight ratio of 60:40. The general chemical formula of the polycrystalline particles is LiNi. 0.85 Co 0.08 Mn 0.05 Al 0.02 O2; The chemical formula of the single crystal particles is LiNi. 0.95 Co 0.02 Mn 0.01 Al 0.01 O2; The electrolyte is 1 mol / L LiPF6, the solvent is EC / DMC / EMC (volume ratio 1:1:1), and 2.0% VC and 5.0% FEC are added; the separator is a polyolefin microporous membrane. The negative electrode sheet includes a negative electrode material, which comprises graphite-based materials, silicon-carbon composite materials, porous carbon materials, and a binder. The graphite-based materials are selected from artificial graphite (median particle size Dv50 of 10-20 μm). The silicon-carbon composite materials are commercially available deposited silicon-carbon materials with a silicon content of approximately 40-60%. The porous carbon materials have a pore size of 20.0 nm, a pore volume of 0.8 cm³ / g, and a BET specific surface area of ​​300 m² / g. The binder is sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR). The negative electrode material contains 86.5 wt% graphite-based materials, 10.0 wt% silicon-carbon composite materials, 1.5 wt% porous carbon materials, and the remainder is binder.

[0046] Example 12

[0047] A 21650 all-tab cylindrical lithium-ion battery is provided, the battery comprising a battery casing and a battery core and electrolyte encapsulated in the battery casing; The battery casing has an outer diameter of 21.2 mm and a height of 65.2 mm. The battery core has an energy density of 275 Wh / kg. The ratio of the energy density of the battery core to the volume of the battery casing is approximately 11.95 Wh / (kg·cm³). The battery core includes a positive electrode sheet, a negative electrode sheet, and a separator. The positive electrode sheet includes a positive electrode active material, which, by weight 100, is composed of a mixture of polycrystalline particles and monocrystalline particles in a weight ratio of 80:20. The general chemical formula of the polycrystalline particles is LiNi. 0.90 Co 0.03 Mn 0.03 Al 0.02 O2; The chemical formula of the single crystal particles is LiNi. 0.92 Co 0.03 Mn 0.02 Al 0.03 O2; The electrolyte is 1 mol / L LiPF6, the solvent is EC / DMC / EMC (volume ratio 1:1:1), and 2.0% VC and 5.0% FEC are added; the diaphragm is a ceramic-coated diaphragm. The negative electrode sheet includes a negative electrode material, which comprises graphite-based materials, silicon-carbon composite materials, porous carbon materials, and a binder. The graphite-based materials are selected from artificial graphite (median particle size Dv50 of 10-20 μm). The silicon-carbon composite materials are commercially available deposited silicon-carbon materials with a silicon content of approximately 40-60%. The porous carbon materials have a pore size of 30.0 nm, a pore volume of 0.5 cm³ / g, and a BET specific surface area of ​​500 m² / g. The binder is sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR). The negative electrode material contains 86.0 wt% graphite-based materials, 8.0 wt% silicon-carbon composite materials, 4.0 wt% porous carbon materials, and the remainder is binder.

[0048] Example 13

[0049] A 21650 all-tab cylindrical lithium-ion battery is provided, the battery comprising a battery casing and a battery core and electrolyte encapsulated in the battery casing; The battery casing has an outer diameter of 21.0 mm and a height of 65.0 mm. The battery core has an energy density of 330 Wh / kg. The ratio of the energy density of the battery core to the volume of the battery casing is approximately 14.67 Wh / (kg·cm³). The battery core includes a positive electrode sheet, a negative electrode sheet, and a separator. The positive electrode sheet includes a positive electrode active material, which, by weight 100, is composed of a mixture of polycrystalline particles and monocrystalline particles in a weight ratio of 85:15. The general chemical formula of the polycrystalline particles is Li 0.95 Ni 0.92 Co 0.04 Mn 0.03 Al 0.01 O2; The chemical formula of the single crystal particles is Li 0.95 Ni 0.93 Co 0.04 Mn 0.02 Al 0.01 O2; The electrolyte is 1 mol / L LiPF6, the solvent is EC / DMC / EMC (volume ratio 1:1:1), and 2.0% VC and 5.0% FEC are added; the separator is a polyolefin microporous membrane. The negative electrode sheet includes a negative electrode material, which comprises graphite-based materials, silicon-carbon composite materials, porous carbon materials, and a binder. The graphite-based materials are selected from artificial graphite (median particle size Dv50 of 10-20 μm). The silicon-carbon composite materials are commercially available deposited silicon-carbon materials with a silicon content of approximately 40-60%. The porous carbon materials have a pore size of 5.0 nm, a pore volume of 0.3 cm³ / g, and a BET specific surface area of ​​400 m² / g. The binder is sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR). The negative electrode material contains 88.5 wt% graphite-based materials, 8.0 wt% silicon-carbon composite materials, 3.0 wt% porous carbon materials, and the remainder is binder.

[0050] Comparative Example 1

[0051] The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, an equal amount of Super P conductive carbon black was used to replace the porous carbon material, while the rest was the same as in Example 1.

[0052] Comparative Example 2

[0053] The difference between Comparative Example 2 and Example 1 is that no porous carbon material is added in Comparative Example 2, and the amount of porous carbon material added is increased to graphite material. Otherwise, it is the same as Example 1.

[0054] Comparative Example 3

[0055] The difference between Comparative Example 3 and Example 1 is that the amount of porous carbon material added in Comparative Example 3 is 8.0 wt%, while the content of graphite material is reduced to 80.0 wt%, and the rest is the same as in Example 1.

[0056] Comparative Example 4

[0057] The difference between Comparative Example 4 and Example 1 is that Comparative Example 4 uses an equal amount of microporous carbon (pore size < 2.0 nm) instead of porous carbon material, while the rest is the same as Example 1.

[0058] Comparative Example 5

[0059] The difference between Comparative Example 5 and Example 1 is that the ratio of the energy density of the battery core to the volume of the battery casing in Comparative Example 5 is approximately 16.5 Wh / (kg·cm³), while the other conditions are the same as in Example 1.

[0060] Comparative Example 6

[0061] The difference between Comparative Example 6 and Example 1 is that the ratio of the energy density of the battery core to the volume of the battery casing in Comparative Example 6 is approximately 11.3 Wh / (kg·cm³), while the other conditions are the same as in Example 1.

[0062] The specific surface area and pore structure of the porous carbon materials in Examples 1-10 and Comparative Examples 1-6 were tested using the nitrogen adsorption method (BET method, referring to GB / T 19587-2017 standard) to determine the specific surface area, pore volume and pore size distribution of the powder samples.

[0063] test: Electrochemical performance tests were conducted on the batteries of Examples 1-10 and Comparative Examples 1-6: ① Electrochemical performance test: Using lithium metal as the counter electrode, constant current charge-discharge tests were performed at 25°C, with a charge-discharge voltage range of 0.01-1.5V. The first cycle was activated at a rate of 0.1C, and subsequent cycles were performed at the specified rate; ② Cycle performance test: 200 cycles were performed under constant current charge-discharge conditions at 0.5C, and the capacity retention rate of each cycle was calculated based on the reversible capacity of the first cycle; ③ Rate performance test: 5 cycles were performed sequentially at rates of 0.1C, 0.2C, 0.5C, 1C, and 2C, and finally 5 cycles were performed at 0.1C. The rate capacity retention rate was calculated based on the ratio of the capacity of the last cycle at each rate to the capacity at 0.1C; The specific test results are shown in Table 1 below: Table 1 shows the electrochemical performance test results of the batteries in Examples 1-10 and Comparative Examples 1-6.

[0064] The test results in Table 1 show that: (1) Effect of mesoporous carbon replacing conventional conductive agents: In Example 1 and Comparative Example 1, under the same graphite and SiC ratio, after replacing the conventional conductive carbon black of Super P with an equal amount of porous carbon material, the first reversible specific capacity of the battery increased from 519 mAh / g to about 524 mAh / g, an increase of about 5 mAh / g. This is mainly attributed to the additional lithium storage capacity contributed by the porous carbon material itself as an independent active material (the reversible specific capacity of porous carbon is about 220 mAh / g, which is much higher than that of Super P, which is no more than 20 mAh / g). More significantly, the porous carbon material improves the cycle and rate performance: the capacity retention rate after 200 cycles increased from 80% to 88%, an increase of about 8 percentage points; the 1C / 0.1C rate retention rate increased from 73% to 82%, an increase of 9 percentage points. The former is attributed to the physical buffering effect of the mesoporous voids of porous carbon on the volume expansion of SiC, and the latter is attributed to the promoting effect of mesoporous channels on the rapid transport of lithium ions. Comparative Example 2, without any added conductive agent (porous carbon material), showed a sharp drop in capacity retention to 70% after 200 cycles and a rate retention of 60% at 1C / 0.1C, further confirming the crucial role of functional carbon additives (porous carbon materials) in silicon-containing anodes.

[0065] (2) Effect of mesoporous carbon addition: There are differences in the amount of mesoporous carbon added in Examples 1, 2 and 3, reflecting the influence of content changes on electrochemical performance. In terms of reversible capacity, with the change of mesoporous carbon content, the reversible capacity is 525 mAh / g, 524 mAh / g and 513 mAh / g, respectively, showing a slow downward trend. This is because the addition of mesoporous carbon replaces part of the graphite, and the reversible specific capacity of graphite (about 340 mAh / g) is higher than that of mesoporous carbon (about 220 mAh / g). Therefore, the higher the content of mesoporous carbon, the slightly lower the overall capacity. In terms of cycle stability, after the increase of porous carbon content, the capacity retention rate after 200 cycles is 85%, 88% and 91% respectively, showing an upward trend, indicating that the expansion buffering effect and structural stabilization function of mesoporous carbon are enhanced with the increase of content. In terms of rate performance, the 1C / 0.1C retention rate increases from 78% to 82% and 84%, indicating that more mesoporous channels are beneficial to improving lithium-ion transport kinetics at high rates. In Comparative Example 3, when the mesoporous carbon content was further increased to 8.0 wt%, the reversible capacity decreased to 511 mAh / g, the initial coulombic efficiency was 86.1%, and the capacity retention rate after 200 cycles was 90%. Compared with Example 3, both the capacity and initial coulombic efficiency decreased slightly, while the cycle retention rate did not improve further, indicating that there is an optimal upper limit for the mesoporous carbon content. When the mesoporous carbon content exceeds this critical value, the negative impact of the increased specific surface area caused by excessive mesoporous carbon on the initial efficiency is insufficient to be offset by the performance gain. Therefore, limiting the upper limit of mesoporous carbon addition to 5.0 wt% has substantial critical significance.

[0066] (3) Effect of mesopore size on rate performance: The comparison between Example 1 and Example 6 reveals the significant effect of the pore size of porous carbon materials on lithium-ion transport kinetics. The reversible specific capacity and initial coulombic efficiency of the two are similar, but the 1C / 0.1C rate retention rate of Example 6 is 76%, which is 6 percentage points lower than that of Example 1 (82%). This indicates that the small mesopores of about 3.0 nm limit the rapid transport of lithium ions in the pores to a certain extent. In Comparative Example 4, after replacing the porous carbon in Example 1 with microporous carbon (pore size < 2.0 nm), the 1C / 0.1C rate retention rate further decreased to 68%, and the capacity retention rate after 200 cycles was only 78%, which was significantly lower than that in Example 1. This indicates that mesoporous structures with pore sizes greater than 2.0 nm are crucial for ensuring rapid lithium-ion transport and effective volume expansion buffering: although micropores can provide a certain specific surface area, their narrow channels create significant diffusion resistance for solvated lithium ions, and the micropore space is insufficient to accommodate the volume changes after the expansion of the silicon-carbon composite material; while mesopores with pore sizes greater than 2.0 nm have the dual functions of lithium storage space and ion transport channels.

[0067] (4) Adaptability of mesoporous carbon with different silicon-carbon composite (SiC) contents: In Examples 4, 1, and 5, the universality of porous carbon in systems with different SiC contents was investigated with a fixed addition of 2.5 wt% porous carbon. As the SiC content increased from 5.0 wt% in Example 4 to 12.0 wt% in Example 1 and 20.0 wt% in Example 5, the reversible capacity of the anode increased from 413 mAh / g to 524 mAh / g and 634 mAh / g, respectively, showing an upward trend. This is attributed to the increased contribution of high-capacity SiC. In terms of cycle stability, the capacity retention rates after 200 cycles corresponding to SiC additions of 5.0 wt%, 12.0 wt%, and 20.0 wt% were 92%, 88%, and 82%, respectively, showing a typical pattern of increased cycle decay of the anode with increasing SiC content. However, with the addition of 2.5 wt% porous carbon, a high SiC content of 20.0 wt% still maintained an 82% cycle retention rate, significantly better than the expected cycle performance without mesoporous carbon or using conventional conductive agents. Meanwhile, the initial coulombic efficiency (ICE) decreased sequentially from 87.9% to 86.3% and then to 85.0%, reflecting the increased irreversible lithium consumption due to the increased SiC content. These results validate that porous carbon, as an independent active material, can effectively play multiple roles as a buffer against volume expansion, a supplement to capacity, and an improvement in ion transport across a wide content range from low to high silicon.

[0068] (5) Effect of specific surface area of ​​porous carbon materials: Examples 9 (BET specific surface area 100 m² / g), 1 (BET specific surface area 300 m² / g), and 10 (BET specific surface area 1000 m² / g) revealed the influence of the specific surface area of ​​porous carbon on electrochemical performance. As the BET specific surface area increased from 100 m² / g to 300 m² / g and 1000 m² / g, the initial reversible capacity increased from 519 mAh / g to 524 mAh / g and 530 mAh / g, respectively, while the initial coulombic efficiency decreased from 86.8% to 86.3% and 85.5%, respectively. In terms of cycle stability, the capacity retention rates after 200 cycles were 87%, 88%, and 86%, respectively, with the optimal value at BET of 300 m² / g. Rate performance increased slightly with increasing BET, indicating that more mesoporous channels are beneficial for ion transport. In summary, when the BET specific surface area is controlled at 300–500 m² / g, the optimal balance between capacity contribution and first coulombic efficiency (ICE) can be achieved; when BET ≤ 1000 m² / g, the ICE can still be maintained at an acceptable level of over 85%, and the lithium storage function and structural buffering effect of mesoporous carbon can be effectively utilized.

[0069] (6) Verification of the pore size boundary values ​​of porous carbon: Examples 7 (pore size 50.0 nm), 1 (pore size 1.0 nm), and 8 (pore size 2.0 nm) further verified the upper and lower boundary effects of the porous carbon pore size; the 1C / 0.1C rate retention rate of Example 7 was 83%, comparable to 82% of Example 1; the capacity retention rate after 200 cycles was 89%, slightly higher than 88% of Example 1. This indicates that large mesopores (close to the upper limit of 50.0 nm) can still provide good ion transport channels and sufficient expansion buffer space, and the mesoporous characteristics at 50.0 nm did not disappear. Functional degradation occurred. The 1C / 0.1C rate retention rate of Example 8 was 72%, significantly lower than that of Example 1, but still better than that of the microporous carbon in Comparative Example 4. The capacity retention rate after 200 cycles was 85%, which was between that of Example 1 and Comparative Example 4. This proves that 2.0 nm pore size is a critical lower limit for mesoporous structures: when the pore size is <2.0 nm, the channels form a significant diffusion resistance to solvated lithium ions and the microporous space is insufficient to accommodate the volume change after SiC expansion; while when the pore size is ≥2.0 nm, the mesoporous structure can effectively perform multiple functions of lithium storage, buffering and ion transport.

[0070] like Figures 1-5As shown, the 21650 cylindrical lithium-ion battery designed in this invention is a full-tab battery with an outer diameter of 21.0 mm ± 0.2 mm and a height of 65 mm ± 0.2 mm. The battery includes a battery casing 1 and a battery core 2. The battery core 2 includes a positive electrode sheet 21 and a negative electrode sheet 22. The positive electrode sheet 21 includes a positive active material layer region 211, an uncoated positive electrode region (positive tab flattened region) 212, and a positive electrode insulating coating region 213. The area of ​​the uncoated positive electrode region 212 is 3-11% of the area of ​​the positive electrode sheet; the area of ​​the insulating coating region 213 is 1.7-6.9% of the area of ​​the positive electrode sheet, and the insulating coating 213 includes boehmite / alumina and a binder; the negative electrode sheet 22 includes a negative electrode active material layer region 221 and an uncoated negative electrode region (negative electrode tab flattening region) 222, wherein the area of ​​the uncoated negative electrode region 222 is 3.5-10.2% of the area of ​​the negative electrode sheet. The uncoated positive electrode region 212 is the positive electrode tab region, and the uncoated negative electrode region 222 is the negative electrode tab region. Both uncoated regions are formed into full tabs through flattening or cutting and stacking processes.

[0071] The above-described preferred embodiments of the present invention are for illustrative purposes only and are not intended to limit the scope of the invention. Any obvious variations or modifications derived from the technical solutions of the present invention are still within the protection scope of the present invention.

Claims

1. A 21650 all-tab cylindrical lithium-ion battery, characterized in that, The battery includes a battery casing and a battery core and electrolyte encapsulated in the battery casing; The outer diameter of the battery casing is 20.8–21.2 mm and the height is 64.8–65.2 mm. The energy density of the battery core is 270–330 Wh / kg. The energy density of the battery core to the volume ratio of the battery casing is 11.9–14.8 Wh / (kg·cm³). The battery core includes a positive electrode sheet, a negative electrode sheet, and a separator. The positive electrode sheet includes a positive electrode active material. Based on 100g by weight, the positive electrode active material is composed of polycrystalline particles and monocrystalline particles mixed in a weight ratio of (60-85):(15-40). The general chemical formula of the polycrystalline particles is Li a Ni b Co c Mn d Al e O2, where 0.95≤a≤1.05, 0.85≤b≤0.92, 0.03≤c≤0.10, 0.01≤d≤0.10, 0.01≤e≤0.05, b+c+d+e=1; The chemical formula of the single crystal particles is Li x Ni y Co z Mn m Al n O2, in the formula, 0.95≤x≤1.05, 0.85≤y≤0.95, 0.02≤z≤0.08, 0.01≤m≤0.06, 0.01≤n≤0.04, y+z+m+n=1; The negative electrode sheet includes a negative electrode material, which includes at least graphite-based materials, silicon-carbon composite materials, and porous carbon materials. The pore size of the porous carbon material is 2-50 nm, and the content of the porous carbon material in the negative electrode material is 0.5-5.0 wt%.

2. A 21650 all-tab cylindrical lithium-ion battery according to claim 1, characterized in that, The BET specific surface area of ​​the porous carbon material is ≤1000m² / g.

3. A 21650 all-tab cylindrical lithium-ion battery according to claim 2, characterized in that, The BET specific surface area of ​​the porous carbon material is 300-500 m² / g.

4. A 21650 all-tab cylindrical lithium-ion battery according to claim 1, characterized in that, The porous carbon material has a pore volume ≥ 0.1 cm³ / g.

5. A 21650 all-tab cylindrical lithium-ion battery according to claim 1, characterized in that, The content of the silicon-carbon composite material in the negative electrode material is 5.0 to 20.0 wt%.

6. A 21650 all-tab cylindrical lithium-ion battery according to claim 1, characterized in that, The porous carbon material has a pore size of 2–10 nm.

7. A 21650 all-tab cylindrical lithium-ion battery according to claim 1, characterized in that, The full width at half maximum (FWHM) of the pore size distribution of the porous carbon material is ≤5.0 nm.

8. A 21650 all-tab cylindrical lithium-ion battery according to claim 1, characterized in that, The graphite material is at least one of artificial graphite or natural graphite.

9. A 21650 all-tab cylindrical lithium-ion battery according to claim 1, characterized in that, The method for preparing the negative electrode sheet includes: mixing graphite-based materials, silicon-carbon composite materials and porous carbon materials in a solvent to prepare a negative electrode slurry, coating the negative electrode slurry onto the surface of a negative electrode current collector, and drying it to obtain a negative electrode sheet for a lithium-ion battery.

10. A 21650 all-tab cylindrical lithium-ion battery according to claim 9, characterized in that, The battery also meets at least one of the following conditions: (1) The negative electrode slurry also includes a binder, which is selected from sodium carboxymethyl cellulose and / or styrene-butadiene rubber; (2) The electrolyte contains lithium hexafluorophosphate and at least one organic solvent selected from ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate; (3) The diaphragm is a polyolefin microporous membrane or a ceramic-coated diaphragm.